THE ROLE AND IMPORTANCE OF METEOROLOGY IN MODERN ARMED CONFLICTS - Turgun Bahriddinovich Khafizov; Po‘latov Ilxomjon Mamadaminovich (Modern American Journals, 2025)
This article analyzes the importance of meteorology in modern armed conflicts, its impact on military strategy and tactics, including the effectiveness of weapons, and its role in choosing the time and location of hostilities. The article also discusses the presentation of meteorological data in real time and their importance for military intelligence using satellite technology.
Keywords: Modern armed conflicts, meteorology, military meteorology, combat conditions, air situation, operational data, military tactics, climate impact, military operations, meteorological data, aviation forecasts, success factors, security, strategic planning, military practice.